Assisted Partner Notification for HIV: a qualitative study of providers and female patients perspectives and experiences of assisted partner notification in Cape Town, South Africa - Perera, Shehani (Department of Public Health and Family Medicine, 2025)
Background Assisted partner notification (APN) is a partner notification approach where trained providers assist individuals newly diagnosed with HIV to notify their partners and then link these partners to testing and treatment services. APN has been found to be more effective at increasing HIVtesting and linkage to care rates than passive referral, where HIV-positive individuals notify partners themselves. In 2016, the WHO published official APN guidelines recommending APN for HIV. However, various factors have influenced the implementation of APN such as human rights concerns and ethical dilemmas, fear of social harm, intimate partner violence or relationship dissolution, and social and cultural factors such as gender. In South Africa, there are no specific guidelines or policies informing the implementation of APN and we are unsure about how implementation unfolds. This study sought to better understand APN by exploring patients' and providers' experiences and perceptions of APN, taking into consideration different factors that shape partner notification documented in local and international literature. The influence of religion and faith and the involvement of faith-based organisations, as well as the impact of the COVID-19 pandemic on APN for HIV also feature in this study. Methods Qualitative research methods were used in this study. Thirty-four individual, semi-structured interviews with providers (n=10), female patients (n=12) and key informants (n=12) were conducted between March 2021 and February 2022. A diary study using the WhatsApp social media platform and fieldwork journals served to triangulate the interview data collected. Data analysis involved thematic analysis incorporating an intersectional lens. The data were transcribed, then coded using NVivo software. The codes were subsequently organised into overarching themes and sub-themes. Ethics approval was obtained from the Human Research Ethics Council at the University of Cape Town (HREC Ref: 840/2020) and the City of Cape Town (Ref: 28185). Results The study found that while there are no official APN guidelines in this setting, an unofficial APN process unfolded, nevertheless. Patients' views of APN were varied; some felt providerassistance for partner notification was not required at all, others felt it was required if their attempts to notify partners failed and a few saw it as a form of interference in their personal and sexual lives. Relationship type and pre-marital HIV-testing were found to influence patients' decision-making around APN engagement. Insider and outsider narratives emerged revealing the complexities involved in making decisions about who to include or exclude during APN. Providers were found to play several roles during APN: education, facilitation/mediation, and protection. Providers also expressed how their relationships with patients could considerably influence whether patients would notify partners. Factors influencing providers' willingness to offer assistance during APN included fears of causing negative events in patients' relationships and partners not maintaining confidentiality after being notified. Providers employed various trust-building strategies to navigate these concerns. Power imbalances and gendered assumptions of health service use influenced APN substantially. Women took on a central role in partner notification due to greater healthcare involvement and societal beliefs around healthcare practices. Female patients often communicated HIV matters with female providers, revealing that caregiving roles were mostly played by women in APN. Indirect and social media based-partner notification as well as 'collusion testing', where providers and patients colluded to bring partners to clinics for testing, emerged as strategies to fulfil rights and responsibilities related to APN. While some of these effectively linked sexual partners to testing and care, it raised ethical concerns about partners' rights. Provision of APN was also found to be different between non-faith-based and faith-based providers who offered either biomedical care or a form of 'umbrella care' which incorporated biomedical and psychosocial and emotional care, respectively. The moralisation of HIV and certain sexual behaviours using religion as a moral framework imposed a sense of obligation to engage in APN. Participants were ambivalent about the involvement of church elders or pastors in APN, seeing providers as being more appropriate due to their HIV-related training. However, many acknowledged the importance of religious support in motivating them to notify partners and finding hope and resilience, if diagnosed with HIV. Conclusion This study highlights the need for clear and context-specific guidelines in implementing APN. The absence of such guidelines resulted in uncertainty among both patients and providers, hindering their participation in APN. While existing policies mention APN, the study highlights partial and limited implementation, calling attention to the need for improved, localised strategies. Trust emerged as the cornerstone of the APN process, shaping both patient and provider engagement. Trust-building strategies were important for establishing a secure environment for APN. Furthermore, the study revealed gendered dynamics in APN through which care responsibilities such as mediating between providers and male sexual partners further exacerbated the feminization of HIV. Thus, the desire for greater control, agency, and shared decision-making became evident. The exploration of FBOs in APN provision also suggests the importance of holistic care, considering spiritual and medical dimensions of healthcare journeys. Drawing parallels between COVID-19 and HIV contact tracing, the study emphasises the unique challenges posed by different contexts.